Cellular Stress and p53-Associated Apoptosis by Juniperus communis L. Berry Extract Treatment in the Human SH-SY5Y Neuroblastoma Cells - Lantto, Tiina A. (Int J Mol Sci, 2016)
Plant phenolics have shown to activate apoptotic cell death in different tumourigenic cell lines. In this study, we evaluated the effects of juniper berry extract (Juniperus communis L.) on p53 protein, gene expression and DNA fragmentation in human neuroblastoma SH-SY5Y cells. In addition, we analyzed the phenolic composition of the extract. We found that juniper berry extract activated cellular relocalization of p53 and DNA fragmentation-dependent cell death. Differentially expressed genes between treated and non-treated cells were evaluated with the cDNA-RDA (representational difference analysis) method at the early time point of apoptotic process when p53 started to be activated and no caspase activity was detected. Twenty one overexpressed genes related to cellular stress, protein synthesis, cell survival and death were detected. Interestingly, they included endoplasmic reticulum (ER) stress inducer and sensor HSPA5 and other ER stress-related genes CALM2 and YKT6 indicating that ER stress response was involved in juniper berry extract mediated cell death. In composition analysis, we identified and quantified low concentrations of fifteen phenolic compounds. The main groups of them were flavones, flavonols, phenolic acids, flavanol and biflavonoid including glycosides of quercetin, apigenin, isoscutellarein and hypolaetin. It is suggested that juniper berry extract induced the p53-associated apoptosis through the potentiation and synergism by several phenolic compounds.